The Relationship Between Health Beliefs and COVID-19 Prevention Behaviors among Pregnant Women Attending Antenatal Services at Hospitals in Chiang Mai Province - Kowatcharakul, Supranee; Sinthubua, Supattra; Kabmala , Prapaisri; Maka, Yaowaluck (Journal of Nursing and Public Health Research, 2025)
This cross-sectional descriptive study aimed to examine health beliefs regarding COVID-19 prevention, COVID-19 preventive behaviors, and the relationship between health beliefs and preventive behaviors among pregnant women attending antenatal care clinics in hospitals in Chiang Mai Province. The sample consisted of 380 pregnant women receiving antenatal care services at 23 hospitals in Chiang Mai, selected through simple random sampling. Data were collected using two questionnaires: one assessing health beliefs related to COVID-19 prevention and the other measuring COVID-19 preventive behaviors among pregnant women. Data were analyzed using mean, standard deviation, and Spearman’s rank correlation coefficient. The results revealed that the overall health beliefs regarding COVID-19 prevention among pregnant women were at a high level (Mean = 3.10, S.D. = 0.21). When considering each dimension, it was found that perceived benefits of appropriate preventive practices, perceived susceptibility to infection, perceived cues to action, and perceived severity and complications of the disease were all at a high level, with mean scores and standard deviations of 3.57 (S.D. = 0.44), 3.39 (S.D. = 0.43), 3.31 (S.D. = 0.43), and 3.21 (S.D. = 0.52), respectively. In contrast, perceived barriers to practicing appropriate COVID-19 prevention were at a moderate level (Mean = 2.72, S.D. = 0.56). Preventive behaviors against COVID-19 among pregnant women were found to be at a high level (Mean = 2.92, S.D. = 0.27). Furthermore, there was a statistically significant low positive correlation between overall health beliefs and COVID-19 preventive behaviors (rs = 0.151, p-value < 0.01). These findings can be applied to promote appropriate health belief patterns among pregnant women, thereby enhancing their correct and appropriate COVID-19 preventive behaviors, which may contribute to better health outcomes for both mothers and their unborn children.